EFEKTIVITAS MEDIA FLASHCARD BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MENULIS PADA SISWA KELAS III SD NEGERI 5 SONGAN KECAMATAN KINTAMANI KABUPATEN BANGLI - Apriningsih, Ni Putu; Anak Agung Ngurah Budiadnyana; Ni Nyoman Ayu Suciartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effectiveness of pictured flashcard media in improving sentence writing skills among third-grade students at SD Negeri 5 Songan, Kintamani District, Bangli Regency. Students’ writing skills were still relatively low, especially in arranging sentences coherently and developing ideas into written form. This research used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The subjects consisted of an experimental class using pictured flashcard media and a control class using conventional learning methods. Data were collected through pretest and posttest writing assessments and analyzed using normality tests, homogeneity tests, independent t-tests, and N-Gain analysis. The results showed that there was no significant difference in students’ initial writing abilities, with a pretest significance value of 0.398 (>0.05). After treatment, the posttest results showed a significant difference with a significance value of <0.001 (<0.05). The average score of the experimental class was 79.11, while the control class obtained 69.42. Furthermore, the N-Gain score of the experimental class was 0.54, which was higher than the control class score of 0.36. Therefore, pictured flashcard media were proven effective in improving elementary school students’ sentence writing skills.